The effectiveness of rivanol tampon" compared with burowi tampon in acute diffuse otitis externa (ADOE)patients - I Wayan Marthana Kedel, Edhie Samodra Bambang Udji Djoko Rianto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Acute diffuse otitis externa (ADOE) is one of the common diseases in ENT Department, Dr. Sardjito Hospital, with the frequency of 9-1 2%. The most common microorganism found is Pseudomonas aeruginosa. Infection usually occurrs after taking a bath, washing hair, and scratching the external ear canal. Treatment of acute diffuse otitis externa which consists of topical preparations, Le. antibiotics and antiinflammation tampon or ear drop, is relatively expensive. A rationale, high recovery rate, cheap, and easily found preparation is needed. Burowi solution is one of the recommended treatment, but it is less popular. Objective: The goal of this study was to know the effectiveness of Rivanol" tampon compared with Burowi tampon in acute diffuse otitis externa. Methods: A randomized single-blind controlled trial (RCT)was performed at the outpatient clinicof ENTDepartment of DrSardjito General Hospital, Yogyakarta. Sixty-five subjects who were'diagnosed as ADOEwho met inclusion criteria were randomly allocated into two groups, that is, Rivanol"group and Burowi group. The ear canal was cleaned, and then Rivanol"tampon or Burowi tampon was applied. Evaluation was performed on day 3 and 5. Primary outcome was the recovery rate, and secondary outcomes were adverse reaction and marginal costeffectiveness. Results: Of 65 subjects, 33 were alloc'8ted into Rivanol"group and 32 were. allocated into Burowi group. The recovery rate in Rivanol"group was 75.4%, while in Burowigroups was 49.3%. The difference in recovery rate between the two groups was statistically significant (p: 0.018; RR4.350; 95% CI1.225-15.442). Adverse reaction in Rivanol"group was dampness and soggy feeling in the ear canal (1.5%), while in the Burowigroup the adverse events were pain and burnt sensation inthe ear canal (3.1%), but they could be tolerated and disappeared on day 5. Analysis on marginal cost-effectiveness showed that the cost to cure one acute diffuse otitis externa patient with Rivanol"tamponwas Rp 1,000. Conclusion: Rivanol"tampon was more clinicallyeffective and more cost-effective than Burowitampon for acute diffuse otitis externa treatment. Key words: acute diffuse otitis externa, Rivanol(!),Burowi,.clinical and cost effectiveness